Characterization of Electromagnetic Wave in Transformer for Partial Discharge Detection - Suwan, Supakorn; Tiengthong, Thanadol; Southisombath, Phouthong; Promwong, Sathaporn (My University, 2023)
The increasing demand for electricity and the potential risks associated with partial discharge highlights the critical importance of robust transformer condition monitoring. Electromagnetic methods offer a promising approach to monitoring transformer health, benefiting from their ability to minimize external interference and their broad operating bandwidth covering HF, VHF, and UHF frequencies. The IEC 62478 standard provides multiple methodologies to leverage electromagnetic techniques in transformer health assessment, encompassing the analysis of electromagnetic waves through directivity, sensitivity, and transmission properties. In this study, we specifically investigate the transformer's UHF transmission characteristics. A vector network analyzer measures and records both transmitting and receiving elements of the UHF transmission channel and the UHF antenna. The measurements within the transformer tank simulate the realistic transformer environment. An optimum receiver is implemented at the receiver end to optimize the received signal quality. The results are comprehensively evaluated by analyzing the UHF transmission channel's path loss and transmission gain within the transformer. The primary objective of this research is to thoroughly examine the UHF transmission characteristics for efficient transformer condition monitoring, offering valuable insights for researchers and engineers involved in mitigating the risks associated with partial discharge in transformers.
Keywords: electromagnetic methods; optimum receiver; partial discharge; path loss; transmission gain